PENGARUH MODEL PEMBELAJARAN TIPE TAKE AND GIVE BERBASIS PENDIDIKAN KARAKTER TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN KIMIA - Ambarwati, Eni; Yusrin, Yusrin; Winaryati, Eny (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Variations of learning model can be used to provide convenience to students infollowing the learning and can overcome the difficulties experienced by students during learning, one of the models of learning that can be applied is cooperative learning model Take And Give type. The purpose of this research is to know the effect of Take And Give learning model based on Character Education toward students' motivation and learning outcomes in chemistry learning. The research design used is a quasi-experimental research. The population in this study is class X consisting of five classes in SMK Negeri 1 Buru. The results of the study found that the take and give learning method proved effective and significant in improving students' motivation andachievement. Based on the results of these studies it is expected that teachersshould be more varied in providing learning methods should be more varied sothat students do not experience saturation at the time of delivery of the material. Keywords: Take and Give, Motivation, Learning Outcomes